Enhancing the melt crystallization of polymers, especially slow crystallizing polymers like PLLA and PET. Issue 1 (10th December 2019) - Tonelli, Alan E.
Abstract: Over 20 years ago we demonstrated that it is possible to control the melt crystallization of polymers via self‐nucleation. Non‐covalently bonded inclusion compounds (ICs) can be formed with cyclodextrins (CDs) or urea (U) when these small host molecules crystallize around guest polymers and form narrow parallel host channels, where the isolated and stretched guest polymer chains are included. Careful removal of the host crystalline lattice yields a neat coalesced (c) guest polymer sample with less entangled chains that are packed to a higher density than bulk samples of the same polymer obtained from its melt or solutions. Consequently, the reorganized c‐polymer samples behave distinctly, with higher glass‐transition temperatures for amorphous polymers and enhanced crystallizabilities for semi‐crystalline polymers. Remarkably, c‐polymer samples retain their distinct reorganized structures and behaviors even after extended periods of melt annealing. When a small amount of the rapidly crystallizable c‐polymer is homogeneously dispersed in a large quantity of the same as‐received (asr) polymer, and it is melted and then cooled, the c‐polymer chains crystallize first and nucleate the crystallization of the asr‐polymer chains, so that the entire sample (nuc‐polymer) crystallizes at nearly the same temperature as the neat nucleant (c‐polymer), including slow melt‐crystallizing polymers, such as PET and PLLA. Abstract : The authors have demonstrated that it is possible to control the melt crystallization of polymers via self‐nucleation. Non‐covalently bonded ICs can be formed with cyclodextrins (CDs) or U hosts that crystallize around guest polymers and form narrow parallel host channels, where the isolated and stretched guest polymer chains are included. Careful removal of the hosts produce c‐polymer samples that crystallize much faster than their asr‐samples that they are able to nucleate.